-1=6a-1+6a

Simple and best practice solution for -1=6a-1+6a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1=6a-1+6a equation:


Simplifying
-1 = 6a + -1 + 6a

Reorder the terms:
-1 = -1 + 6a + 6a

Combine like terms: 6a + 6a = 12a
-1 = -1 + 12a

Add '1' to each side of the equation.
-1 + 1 = -1 + 1 + 12a

Combine like terms: -1 + 1 = 0
0 = -1 + 1 + 12a

Combine like terms: -1 + 1 = 0
0 = 0 + 12a
0 = 12a

Solving
0 = 12a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-12a' to each side of the equation.
0 + -12a = 12a + -12a
Remove the zero:
-12a = 12a + -12a

Combine like terms: 12a + -12a = 0
-12a = 0

Divide each side by '-12'.
a = 0

Simplifying
a = 0

See similar equations:

| 0.6x-3.9=0.6 | | -8k+26=-8k | | -.5(16-2h)=11 | | 2y+19+y=7y-9 | | 3(x-5)+1=(1/4)(2x-8) | | 11+(7+n)=24 | | -3y+8=-12x | | 4(x-2)/6=2(x+8)/13 | | 2x^2+2x=-74 | | (3/4)(4-x)=3-x | | 4(x-3)+2x=3(2x-5) | | 36x-63=36x+18 | | 3s(2)-5s+9=0 | | 3c(x+2)-5=c(x-3) | | 2=-5n+4n | | 5.5=-2+d | | 4(3q-2)=16 | | x^2-7x+1.25=0 | | 5.4t+14.6-10.1t=12.8-3.5t | | -2--14= | | 4(x+1)/6=3x-4 | | -2+-14= | | 50,000=28 | | 5(3+5x)-5=160 | | 2a-9=2a-9 | | 0.50x+0.35(70)=47.5 | | 6=.0002x^2-.316x+127.9 | | 24=7x-4(2x-4) | | 3x=4y | | 4x-6=9x+1 | | 2(4x-3)-8=-3(4x-5) | | -p-6p=0 |

Equations solver categories